A Comparison of the Validity of Very Brief Measures of the Big Five/Five-Factor Model of Personality. (April 2021) - Sleep, Chelsea E.; Lynam, Donald R.; Miller, Joshua D.
Personality is of great lay, clinical, and research interest with important functional implications. The field has largely settled on five- or six-factor models as being largely sufficient for descriptive purposes, at least in W.E.I.R.D settings and, as such, numerous measures have been created of varying length and breadth. For a number of reasons, however, super-short forms have come to be quite popular in research endeavors with a number created in the past 20 years. The goal of the present study was to compare the time with completion and general psychometric properties of these measures, as well as examine their convergence with one another and with longer measures in an online community sample ( N = 494). Generally, the psychometric properties of the measures varied considerably in terms of internal consistency and convergence with one another. The brief measures demonstrated mostly adequately convergence with longer measures. Despite this convergence, longer measures were found to contain considerably more variance that was not accounted for by brief measures. We consider the advantages and disadvantages of these measures and suggest that longer measures be prioritized whenever possible.